2021
DOI: 10.1080/21505594.2021.1936767
|View full text |Cite
|
Sign up to set email alerts
|

YhjC is a novel transcriptional regulator required for Shigella flexneri virulence

Abstract: Shigella is an intracellular pathogen that primarily infects the human colon and causes shigellosis. Shigella virulence relies largely on the type III secretion system (T3SS) and secreted effectors. VirF, the master Shigella virulence regulator, is essential for the expression of T3SS-related genes. In this study, we found that YhjC, a LysR-type transcriptional regulator, is required for Shigella virulence through activating the transcription of virF. Pathogenicity of the yhjC mutant, including colonization in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The factors that have effect on the expression of the yhjC gene are unknown, however, it has been observed that expression of this gene increases, when the temperature rises from 30 to 37 degrees. These ndings increase the prospect that this gene is under control of a twocomponent regulation system CpxA/R (34). In the present study, temperature, pH, and osmolarity for all antibiotic-treated and untreated samples were equal, thus, the probability that Sub-MICs of antibiotics alter virF expression via CpxA/R, is diminished.…”
Section: Discussionmentioning
confidence: 46%
“…The factors that have effect on the expression of the yhjC gene are unknown, however, it has been observed that expression of this gene increases, when the temperature rises from 30 to 37 degrees. These ndings increase the prospect that this gene is under control of a twocomponent regulation system CpxA/R (34). In the present study, temperature, pH, and osmolarity for all antibiotic-treated and untreated samples were equal, thus, the probability that Sub-MICs of antibiotics alter virF expression via CpxA/R, is diminished.…”
Section: Discussionmentioning
confidence: 46%
“…The adhesion and invasion capacities of each strain were measured according to the previous method. 35 , 36 Briefly, overnight cultures of each strain were subcultured to the OD 600 of 1. The culture medium underwent centrifugation at 4000 ×g for 5 min, and fresh DMEM was introduced to suspend the cell pellets.…”
Section: Methodsmentioning
confidence: 99%
“…Salmonella Typhimurium ATCC 14028s was used as the wild-type (WT) strain in this study. The mutant strain was generated using the λ Red recombinase system supported by the pSim17 plasmid (blastidin-resistant) encoding three proteins (Exo, Beta, and Gam) that are required for homologous recombination [42]. First, a WT strain harboring the pSim17 plasmid was established through electrotransformation.…”
Section: Bacterial Strains and Plasmidsmentioning
confidence: 99%